ILLOCUTIONARY ACTS OF HATE SPEECH: ANALYZING SOCIAL MEDIA COMMENTARY TARGETING ANIES BASWEDAN - Fatimah Sari Siregar; Edy Suprayetno; Erlindawaty Erlindawaty; Fahrus Zaman Fadhly (University of Kuningan, 2024)
This study aimed to describe the types of illocutionary hate speech acts in social media comments. Qualitative design is conducted in this research. The technique of data collection are free listening techniques (Simak Bebas Libat Cakap) and recording techniques. Data analysis techniques in this study used metode padan and metode agih. The types of illocutionary was assertive that were boasting, complaining, stating, and suggesting, expressive that was blaming, and declaration that was excommunicating. The most common language was found to be more dominant in assertive speech acts. The number was more found, namely 32 assertive speech act quotes about boasting, complaining, stating and suggesting. Expressive speech acts are found only in the blame part. In detail, the expressive part of blaming can be explained, there are 17 quotes. The speech act of the declaration of the excommunication section has 6 quotations.Keywords: Hate speech acts; speech acts; social media